Risk management and big data - Baldwin, Scott (Henry Stewart Talks, 2017)
Business continuity, Business impact analysis, Types of impacts, Direct revenue impacts, Impact over time, Indirect financial impacts, Non-financial impacts, Reputational impacts, Business impact analysis output, Recovery plan, Risk identification, Creating readiness